1988
DOI: 10.1002/ijc.2910420319
|View full text |Cite
|
Sign up to set email alerts
|

Effect of retinoids on the proliferation, morphology and expression of glial fibrillary acidic protein of an anaplastic astrocytoma cell line

Abstract: We studied the effect of retinoids on the growth and differentiation of a cell line (U 343 MG-A) derived from a human malignant astrocytoma. Cultures treated with all-trans or 13-cis retinoic acid showed a dose-dependent inhibition of proliferation and a marked reduction in the mean cell number at the plateau phase of growth (3.5 x 10(6) vs. 1 x 10(7) cells/25 cm2) compared with untreated cultures. At confluence, cells treated with all-trans or 13-cis retinoic acid were contact-inhibited, whereas control cultu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
28
0
1

Year Published

1993
1993
2010
2010

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 53 publications
(31 citation statements)
references
References 43 publications
2
28
0
1
Order By: Relevance
“…This would explain the previous observation of increased GFAP expression and moderate growth inhibition in a glioma cell line (U343 MG-A) treated with RA. 20 and represents a novel mechanism of action of RA in glioma therapy. In addition, since the cytoplasmic translocation of N-CoR is triggered by phosphatidyl-inositol-3-OH kinase/Akt1 kinase-dependent phosphorylation, we examined the effect of okadaic acid, a protein phosphatase-1 inhibitor.…”
Section: Resultsmentioning
confidence: 99%
“…This would explain the previous observation of increased GFAP expression and moderate growth inhibition in a glioma cell line (U343 MG-A) treated with RA. 20 and represents a novel mechanism of action of RA in glioma therapy. In addition, since the cytoplasmic translocation of N-CoR is triggered by phosphatidyl-inositol-3-OH kinase/Akt1 kinase-dependent phosphorylation, we examined the effect of okadaic acid, a protein phosphatase-1 inhibitor.…”
Section: Resultsmentioning
confidence: 99%
“…The p16-de®cient, human astrocytoma cell line U343 responds to all-trans RA treatment (Rutka et al, 1988). Figure 1 shows that RA inhibits U343 proliferation ( Figure 1a) and induces morphological changes (Figure 1b ± c).…”
Section: Retinoic Acid Alters the Morphology And Growth Characteristimentioning
confidence: 99%
“…Retinoic acid (RA) treatment of these cells inhibits proliferation, alters morphology, and increases the expression and organization of a marker of glial di erentiation, glial ®brillary acidic protein (GFAP) (Rutka et al, 1988). In the present study, we sought to determine the relationship between RA-induced di erentiation and the expression of several key cell cycle regulators.…”
Section: Introductionmentioning
confidence: 99%
“…In an earlier study, all-trans and 13-cis retinoic acid (10 -6 M) were effective in decreasing the proliferation of GFAP-positive U-343MG-A astrocytoma cells and in increasing the amount of GFAP produced, as measured by enzyme-linked immunosorbent assay. [97] In another study, it was shown that ECM proteins derived from normal human leptomeningeal cells effectively stopped the proliferation of U-343MG-A astrocytoma cells and induced differentiation of these cells as calculated by a quantitative increase in cellular GFAP. [96,98] The results from these studies suggest that the upregulation of GFAP in GFAP-positive astrocytoma cells is associated with alterations in astrocytoma growth and morphology.…”
Section: Glial Fibrillary Acidic Protein: a Link To Glial Cell Adhesion?mentioning
confidence: 99%